2019
DOI: 10.1007/s40430-019-2056-5
|View full text |Cite
|
Sign up to set email alerts
|

Finding dimensional stability considering deflection effects in cylindrical plunge grinding

Abstract: In spite of the existence of several models to effectively design grinding cycles, they are not frequently adopted in production lines, due to the lack of knowledge, difficulties in determining some input parameters and discrepancies observed in the obtained results during the production of a batch of parts. This paper proposes a contribution to the modeling and simulation of cylindrical plunge grinding cycles in terms of dimensional stability of the process, prediction of the workpiece diameter along the grin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Analysis of many scientists’ research results has shown that much attention is paid to the intensification of cylindrical infeed grinding processes and control of cutting forces in this machining method. In particular, S. da Silva et al [ 21 ] noted that despite the existence of several models for effective grinding cycle design, they are not frequently adopted in production lines due to the lack of knowledge, difficulties in determining some input parameters, and discrepancies observed in the obtained results during the production of a batch of parts. That is why this difficult and time-consuming process requires careful preparation for implementing the machining of out-of-repair machine parts even at the stage of pre-production engineering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analysis of many scientists’ research results has shown that much attention is paid to the intensification of cylindrical infeed grinding processes and control of cutting forces in this machining method. In particular, S. da Silva et al [ 21 ] noted that despite the existence of several models for effective grinding cycle design, they are not frequently adopted in production lines due to the lack of knowledge, difficulties in determining some input parameters, and discrepancies observed in the obtained results during the production of a batch of parts. That is why this difficult and time-consuming process requires careful preparation for implementing the machining of out-of-repair machine parts even at the stage of pre-production engineering.…”
Section: Literature Reviewmentioning
confidence: 99%